(untitled) (Academia Journal of Medicine, 2019)
Background: Brain natriuretic peptide (BNP) is a cardiac hormone secreted from the ventricular myocardium as a response to ventricular volume expansion and pressure overload. Rheumatic heart disease is a major health problem, mostly in developing country like India and particularly in this part of the country. In young age group rheumatic heart disease is the most common cause of cardiac morbidity and mortality. In this study our aim is to measure BNP levels in patients with RHD and to find out whether BNP concentrations correlate with clinical and echocardiographic findings. A total of 88 patients with rheumatic valve disease having different type of single or multivalvular lesions were included in this study. BNP was measured using the chemiluminescence methods (Bayer Centure, Germany) by BNP kit. 2D Echocardiography with colour Doppler was performed in all patients to assess the severity of the valve disease and for the measurement of pulmonary artery pressure. The plasma concentrations of BNP were found significantly higher in patients with aortic stenosis than in control (355.92±204.31pg/ml vs.183.39±93.51pg/ml, p < 0.001). The plasma BNP level was significantly higher in NYHA class IV than in class I (921.50±301.93 in class I and 125.85±52.88 pg/ml, p < 0.001 in class III). The independent determinants of higher BNP levels were NYHA functional class and systolic pulmonary artery pressure in multivariate analysis. Along with these results we got all other relative output which suggested that increased plasma BNP levels in patients with rheumatic heart disease compared with healthy subjects.